CREATIVE TASKS FOR MULTILINGUAL STUDENTS - Paul, L.Y.; Razuvayeva, M.V.; Tauakelov, C.A. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
In this article are given definitions to such concepts as “the multilingual student” and “creative tasks” and alsois consideredthe classification of creative tasks for students of multilingual groups. Further according to classification each of its point has been described, are giventhe examples of concrete creative tasks for teaching a foreign language, which in details describe instructions for their appli-cation.
Keywords: multilingual student; creative task; language skills; oral language development; listening practic; process of writing; process of reading